Physical Conditions and Indoor Air Pollution in house and Pneumonia In Toddlers - Kurnia Nalasari Nalasari; Wiwik Eko Pertiwi (Universitas Airlangga, 2019)
Pneumonia was an acute infectious disease that was still a problem in toddlers. Tegalratu Village was the highest region with Toddlers' pneumonia in Cilegon City. The purpose of this study was to analyze the relationship between house physical conditions and indoor air pollution with pneumonia in toddlers in Tegalratu Ciwandan Village Cilegon City. This study was an observational study with cross sectional design. The sample of this studi were 90 mothers who had toddlers. Interviews and observation needed to data collection. The physical condition of the house were condition of the walls, floors, and ceiling, while the sources of indoor air pollutions were cigarette smoke, cooking fuel smoke, and mosquito repellant smoke. Data analyzed with chi-square test. The result showed that there were 10 toddlers (11,1%) with pneumonia, and the variable that were significantly related to the incidents of pneumonia in toddlers was the condition of ceiling (p=0,016<α). Puskesmas should improve coordination across programs to increase public awareness of importance of environment condition to meet the requirements for the best possible degree of health.